On the hero's journey - Campbell, Joseph, 1904-1987 (Joseph Campbell essentials, 2025)
"A collection of quotes from famed mythologist Joseph Campbell in which he discusses the concept of The Hero's Journey, a recurring motif in myth and legend, and how it can act as a catalyst for transformation in our own lives"-- Provided by publisher.